Design Synthesis and Biological Evaluation of Novel N-Nitro Acid Amide Derivatives as Lead Compounds of Herbicide. (20th June 2016) - Qi, Xiaojuan; Tang, Wenjie; Gao, Shan; Gao, Min; Chen, Changshui; Zhang, Qingye
Abstract : A series of N -nitro acid amide derivatives compounds were synthesized based on the active site of target acetohydroxyacid synthase (AHAS, EC: 2.2.1.6) enzyme. All the structures of newly prepared compounds were thoroughly characterized by satisfied IR and 1 H NMR spectra. The IC50 values against AHAS enzyme and EC50 values for herbicidal activity against Amaranthus mangostanus L. and Sorghum sudanense of all synthesized target compounds were determined. The compoundsII-10, II-21, andII-22 with IC50 values of 7.09 mg/L, 9.07 mg/L, and 9.11 mg/L and the compoundsII-8 andII-22 with EC50 values of 9.87 mg/L and 19.88 mg/L against root of Amaranthus mangostanus L. and Sorghum sudanense were illustrated, respectively. Meanwhile, the possible reasons for the lower activity of compounds were analyzed by molecular docking prediction.